2018
DOI: 10.2174/1570180814666170425160545
|View full text |Cite
|
Sign up to set email alerts
|

New Oxadiazole Derivatives: Synthesis and Appraisal of Their Potential as Antimicrobial Agents

Abstract: Introduction: The escalating threat due to dwindling effect of antibiotics and challenge of tackling rising drug-resistant infections has gathered high focus in current medicinal research. Methods: In an attempt to find new molecules that can defeat microbial resistance, two new series of 2-[2-substituted ethenyl]-5-(substituted methoxy)-1,3,4-oxadiazole derivatives were synthesized. Various aromatic hydrazides were allowed to undergo cyclization to substituted oxadiazole-2- amines in the presence of cyanog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, it is absent in humans, that can contribute with the development of selective drugs against pathogens [ 25 ]. 1,3,4-oxadiazole-based drugs have been widely studied by researchers [ 21 , 22 , 23 , 26 , 27 , 28 , 29 ]. These compounds have a high therapeutic power and broad spectrum of action, such as anticancer, antifungal, antibacterial, antitubercular, anti-inflammatory, antineuropathic, antihypertensive, antihistaminic, antiparasitic, antiobesity, antiviral activity, among others [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is absent in humans, that can contribute with the development of selective drugs against pathogens [ 25 ]. 1,3,4-oxadiazole-based drugs have been widely studied by researchers [ 21 , 22 , 23 , 26 , 27 , 28 , 29 ]. These compounds have a high therapeutic power and broad spectrum of action, such as anticancer, antifungal, antibacterial, antitubercular, anti-inflammatory, antineuropathic, antihypertensive, antihistaminic, antiparasitic, antiobesity, antiviral activity, among others [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all the studied derivatives, 147 showed the most potent antimicrobial activity (MIC = 25 μM) against S. aureus and C. albicans, which was comparable with the Ciprofloxacin (MIC <24 μM) and Fluconazole (MIC <24 μM). The SAR analysis revealed that quinoline containing 1,3,4‐oxadiazole compound ( 147 ) showed better activity than naphthalene containing 1,3,4‐oxadiazoles ( 148 – 153 , MIC >10) against studied microbial strains except E. coli (Dhara et al, 2018).…”
Section: 34‐oxadiazole Derivatives As An Antimicrobial Agentmentioning
confidence: 99%